Keterampilan Berpikir Kritis Siswa SD dalam Pembelajaran IPA Menggunakan E-LKPD dengan Pendekatan Inkuiri Terbimbing - Menik Rohayati; Srihandono Budi Prastowo; Suparti Suparti (Jurnal Paedagogy, 2023)
This study aims to improve students' critical thinking skills by using the e-LKPD guided inquiry approach in learning science in grade IV elementary schools. This research used the research development (Research and Development R&D) method. The research was conducted at three public elementary schools in Banyuwangi Regency, East Java province. The research instrument used pre-test and post-test question sheets. Analysis of the effectiveness of the implementation of E-LKPD data used N-Gain analysis obtained from statistical tests of pre-test and post-test results. The study results at two schools showed that students' critical thinking skills in interpretation and analysis were in the high category, while inference and explanation were in the medium category. In another school, the aspects of interpretation, analysis, and inference were in the high category, while the explanation aspect was in the medium category. Based on these results, e-LKPD with the guided inquiry approach was effectively implemented to improve the critical thinking skills of grade IV elementary school students in science learning.